Transfigured world : Walter Pater's aesthetic historicism - Williams, Carolyn, 1950- (Cornell University Press, 1989)
Exploring the intricacy and complexity of Walter Pater's prose, Transfigured World challenges traditional approaches to Pater and shows precise ways in which the form of his prose expresses its content. Carolyn Williams asserts that Pater's aestheticism and his historicism should be understood as dialectically interrelated critical strategies, inextricable from each other in practice. Williams discusses the explicit and embedded narratives that play a crucial role in Pater's aesthetic criticism and examines the figures that compose these narratives, including rhetorical tropes, structures of argument such as genealogy, and historical or fictional personae.